RETRACTED ARTICLE: E-Blue: Implementation of an Integrated Blue Economy Ecosystem to Increase Coastal MSMEs Competitiveness - Perdana, Tito Aditya; Purusa, Nanda Adhi; Kurniawan, Rudi; Suryawijaya, Tito Wira Eka (Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This study aims to determine the implementation and the right business strategy for sustainable fisheries that adopt the